Cholangiocarcinoma in Young Cats - de Brito Jardim, Mariana Palha; de Carvalho Cid, Gabriela; Oliveira, Maria Correia; de Assunção, Rômulo Ferreira; Lima e Silva, Sheila; Nogueira, Vivian de Assunção; Moreira de Souza, Heloisa Justen (Acta Scientiae Veterinariae, 2019)
Background: Cholangiocellular carcinoma is a malignant tumor that occurs mainly in elderly dogs and cats. Primary hepatobiliary neoplasms are considered rare in felines, although cholangiocarcinoma is the most common tumor type among malignant liver tumors in the species. The objective of this work is to report two cases of cholangiocarcinoma in young domestic cats, with three years old, and to approach clinical and pathological aspects to promote awareness of this type of injury in young animals, with a focus on prevention of predisposing factors. Cases: A 3-year-old male domestic cat (cat 1) had a history of progressive weight loss, persistent vomiting, diarrhea, and episodes of seizure. At the clinical examination was noted moderate degree of jaundice. In the biochemical exams it was verified as alteration hypoproteinemia, increase of urea and hyponatremia. Abdominal ultrasonography revealed a formation in the left epigastric region measuring 8.0 x 5.0 cm, with a diffusely heterogeneous parenchyma, suggestive of hepatic neoplasia, in addition to the presence of free abdominal fluid. Cavity fluid analysis was suggestive of carcinoma. A 3-year-old male domestic cat (cat 2), with history of hyporexia, emaciation and vomiting was taken to care. Physical examination showed moderate dehydration, hypocorous mucosa and presence of abdominal mass on palpation. The animal's serum biochemical assessment were verified as changes, increasing AST. Ultrasonographic examination showed an abdominal mass, located caudally to the spleen, with irregular shape, measuring approximately 4.7 cm suggestive of hepatic neoplasia, in addition to the presence of abdominal fluid. The hepatic cytology performed by fine needle aspiration was suggestive of carcinoma. After the clinical worsening of two cats and due unfavorable prognosis, euthanasia and necropsy were performed. In the macroscopic analysis of cat 1, numerous nodules of whitish and sometimes "umbilicate" coloration were observed in the liver, measuring up to three cm in diameter, distributed randomly by the hepatic parenchyma and with a soft consistency at cut. An ovoid-wicking mass, measuring 6.0 x 7.0 x 5.0 cm in diameter and coloring ranging from white to light brown was checked together. In the macroscopic evaluation of cat 2, numerous coalescing masses of whitish coloring measuring up to 6.0 cm in diameter were observed covering almost every hepatic parenchyma and also affecting the pancreas, with a soft consistency at cut. The microscopic findings of both cats were compatible with the diagnosis of cholangiocarcinoma. Considering the immunohistochemical profile, in both cases there was positivity for the CK Pan antibody and CEA and negativity for the CK20, TTF-1, Hepatocyte specific antigen, CD10 and CD56 antibodies. Discussion: Cholangiocarcinomas usually occur in elderly animals, with a mean age of 9 years, so it may be suggested that the cause of the disease in cat 1 and 2 was possibly related to the early and continuous presence of carcinogens. The biliary duct trematod Platynosomum fastosum, the chemical agents plutonium and americium, intestinal parasites such as Ancylostoma spp. and Trichuris vulpis, as well as the occurrence of chronic inflammations independent of etiology are commonly involved in the occurrence of cholangiocarcinoma. Clinical and anatomopathological observations made evident that these two young cats, with three years old, had metastatic cholangiocarcinoma. Thus, veterinary providers should be aware that this tumor type can occur in young animals and is mindful of means of prevention and / or recommended treatment of predisposing factors.